Cytosine Methylation Within Marine Sediment Microbial Communities: Potential Epigenetic Adaptation to the Environment - Rambo, Ian M.; Marsh, Adam; Biddle, Jennifer F. (Frontiers in Microbiology, 2019)
Marine sediments harbor a vast amount of Earth’s microbial biomass, yet little is understood regarding how cells subsist in this low-energy, presumably slow-growth environment. Cells in marine sediments may require additional methods for genetic regulation, such as epigenetic modification via DNA methylation. We investigated this potential phenomenon within a shallow estuary sediment core spanning 100 years of age. Here we provide evidence of dynamic community m5-cytosine methylation within estuarine sediment metagenomes. The methylation states of individual CpG sites were reconstructed and quantified across three depths within the sediment core. A total of 6,254 CpG sites were aligned for direct comparison of methylation states between samples, and 4,235 of these sites mapped to taxa and genes. Our results demonstrate the presence of differential methylation within environmental CpG sites across an age gradient of sediment. We show that epigenetic modification can be detected within complex environmental communities. The change in methylation state of environmentally relevant genes across depths may indicate a dynamic role of DNA methylation in regulation of biogeochemical processes.